Developing an Android application in conjunction with BLE beacons 2 - Parameswaran, Varshini (Nanyang Technological University, 2024)
Zoos are established all over the world for the protection and conservation of wildlife animals as well as educating the public about the role that they can play by contributing to these efforts. However, there is a lack of measures to keep visitors fully engaged during their visit hence, the above-mentioned objectives are not fulfilled entirely.